Effects of unilateral, bilateral, and combined unilateral+bilateral complex resistance training on bench press and squat strength in adolescent boxers - Liu, Yang; Liu, Xiuxia; Geng, Jiaxian (Frontiers in Physiology, 2024)
Objective: To assess the effects of 8 weeks of unilateral (UNI), bilateral (BI), and combined unilateral+bilateral (UNI+BI) resistance training on bench press and squat strength in adolescent boxers. Methods: Using the Gym Aware linear accelerometer, free-weight squat and bench press strength exercises were evaluated after an 8-week training intervention. Thirty adolescent boxers were randomly assigned to three groups: UNI, height: 1.73±0.08 m, weight: 55.42±5.85 kg; UNI+BI, height: 1.7±0.06 m, weight: 54.73±5.33 kg; and BI, height: 1.74±0.06 m, weight: 59.67±8.39 kg. Each group followed their designated UNI/BI/UNI+BI compound resistance training protocols, and the effects of 8 weeks of single-sided and bilateral intervention training on the performance of freeweight squat and bench press exercises at 30%, 50%, and 80% of 1-repetition maximum (1RM) were evaluated. Results: Significant improvements were observed in the 30% 1RM, 50% 1RM, and 80% 1RM outcomes for both squat and bench press exercises before and after the interventions (p<0.05, p<0.01). In the intergroup comparison, GymAware measurements revealed that the UNI and UNI+BI groups exhibited superior peak power values for squat and bench press exercises at 30% 1RM compared to the BI group. Discussion: UNI and UNI+BI training led to significantly higher output power values in bench press and squat exercises at 30% 1RM compared to the BI training group.